2011
DOI: 10.11646/zootaxa.2827.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A new specimen of the theropod dinosaur Baryonyx from the early Cretaceous of Portugal and taxonomic validity of Suchosaurus

Abstract: Although the Late Jurassic of Portugal has provided abundant dinosaur fossils, material from the Early Cretaceous is scarce. This paper reports new cranial and postcranial material of the theropod dinosaur Baryonyx walkeri found in the Barremian (Papo Seco Formation) of Portugal. This specimen, found at Praia das Aguncheiras, Cabo Espichel, consists of a partial dentary, isolated teeth, pedal ungual, two calcanea, presacral and caudal vertebrae, fragmentary pubis, scapula, and rib fragments. It represents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 26 publications
2
41
0
7
Order By: Relevance
“…Additional finds have been related to named taxa (e.g. Buffetaut, 2008;Mateus et al, 2011) has also extended our knowledge and may yet yield new taxa (see Naish, 2011).…”
Section: Historymentioning
confidence: 93%
See 2 more Smart Citations
“…Additional finds have been related to named taxa (e.g. Buffetaut, 2008;Mateus et al, 2011) has also extended our knowledge and may yet yield new taxa (see Naish, 2011).…”
Section: Historymentioning
confidence: 93%
“…Material now recognised as spinosaur in origin in fact was first described by Richard Owen in the early 1840s based on teeth he obtained from Gideon Mantell (see Buffetaut, 2010 for details). These teeth were considered at the time to belong to a crocodilian (and indeed spinosaur teeth are similar to crocodilians) but may now be referred to Baryonyx (Buffetaut, 2010, Mateus et al, 2011. Similarly, fragmentary teeth from Algeria that belong to Spinosaurus predate Stromer's discoveries (Buffetaut, 2010) and material recovered from the Tendaguru expeditions of the 1920s were only identified as spinosaurid in origin nearly a century later (Buffetaut, 2008), although this referral is controversial (Rauhut, 2011).…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Spinosaurid teeth are also characterized by numerous minute denticles: 7/mm in Baryonyx Milner, 1986, 1997), 6/mm in Suchomimus (Smith et al, 2005: database), and 5-13/mm in indeterminate isolated teeth (Hone et al, 2010;Mateus et al, 2011;Ruiz-Omeñaca et al, 2005), and some are reported unserrated (Spinosaurus Stromer, 1915 andIrritator Sues et al, 2002). TP4-2 has only 2.2 denticles/mm (Fig.…”
Section: Morphotypementioning
confidence: 99%
“…1996;Escaso et al 2005;Torcida Fernández-Baldor 2006;Pereda-Suberbiola et al 2007;Sánchez-Hernández et al 2007;Buscalioni et al 2008;Gasulla et al 2009Gasulla et al , 2011Mateus et al 2011). Holtz et al (2004 proposed that the Greater Wealden, comprising localities of the Lower Cretaceous of England and continental Europe, as well as comparable faunas of southern and central Europe, western North America, and Africa, share a common composition of dinosaur faunas.…”
Section: Palaeobiogeographic Implications-the Recent Studies Ofmentioning
confidence: 99%